A comparative analysis of egg provisioning using mass spectrometry during rapid life history evolution in sea urchins. Issue 4 (17th May 2019) - Davidson, Phillip L.; Thompson, J. Will; Foster, Matthew W.; Moseley, M. Arthur; Byrne, Maria; Wray, Gregory A.
Abstract: A dramatic life history switch that has evolved numerous times in marine invertebrates is the transition from planktotrophic (feeding) to lecithotrophic (nonfeeding) larval development—an evolutionary tradeoff with many important developmental and ecological consequences. To attain a more comprehensive understanding of the molecular basis for this switch, we performed untargeted lipidomic and proteomic liquid chromatography‐tandem mass spectrometry on eggs and larvae from three sea urchin species: the lecithotroph Heliocidaris erythrogramma, the closely related planktotroph Heliocidaris tuberculata, and the distantly related planktotroph Lytechinus variegatus . We identify numerous molecular‐level changes possibly associated with the evolution of lecithotrophy in H. erythrogramma . We find the massive lipid stores of H. erythrogramma eggs are largely composed of low‐density, diacylglycerol ether lipids that, contrary to expectations, appear to support postmetamorphic development and survivorship. Rapid premetamorphic development in this species may instead be powered by upregulated carbohydrate metabolism or triacylglycerol metabolism. We also find proteins involved in oxidative stress regulation are upregulated in H. erythrogramma eggs, and apoB‐like lipid transfer proteins may be important for echinoid oogenic nutrient provisioning. These results demonstrate how mass spectrometry can enrich our understanding of life history evolution and organismal diversity by identifying specific molecules associated with distinct life history strategies and prompt new hypotheses about how and why these adaptations evolve.